Pengaruh Transformational Leadership dan Knowledge Sharing Terhadap Innovation Behavior dengan Creative Self-Efficacy Sebagai Variabel Mediasi pada Karyawan Generasi Z di Daerah Istimewa Yogyakarta - Yaffa Suci Indriastuty; Nur Wening (Jurnal Ragam Pengabdian, 2026)
This study investigates the influence of transformational leadership and knowledge sharing on innovation behavior, with creative self-efficacy serving as a mediating variable among Generation Z employees in the Special Region of Yogyakarta, Indonesia. The research is motivated by Indonesia’s relatively low ranking in the Global Innovation Index within ASEAN and the growing dominance of Generation Z in the workforce. A quantitative approach was employed using purposive sampling, involving 140 respondents who met the study criteria. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that transformational leadership has a positive and significant effect on innovation behavior. Knowledge sharing does not directly influence innovation behavior but significantly enhances creative self-efficacy. Meanwhile, transformational leadership has no significant effect on creative self-efficacy. Creative self-efficacy positively and significantly influences innovation behavior and mediates the relationship between knowledge sharing and innovation behavior, but it does not mediate the relationship between transformational leadership and innovation behavior. Overall, the proposed model explains 40.2% of the variance in innovation behavior among Generation Z employees and provides empirical evidence on the psychological mechanisms linking leadership, knowledge sharing, and innovative behavior in the Indonesian workplace.